Unlocking the potential of translation for FLT - Kocbek, Alenka (Linguistica (Ljubljana), 2014)
The paper proposes unlocking the potential of translation for foreign language teaching (FLT) by seeking to create synergies with the related discipline of translation science (TS). This aim is in keeping with the guidelines for language teaching provided in the Common European Framework of Languages, which introduced a model of communicative competences including communicative language competences as those which enable a person to act by drawing on specific linguistic means. First, an overview of the changing status of translation in FLT is presented - from its being considered a fundamental teaching method and basic skill in the Grammar-Translation Method, to its being all but outlawed in more recent communicative and task-based approaches, to its final rehabilitation in recent decades. It is then shown that, in the development of FLT, the parallel evolution of TS somehow failed to be acknowledged and, consequently, the opportunity to create valuable synergies between the two disciplines was missed. Following the stance of authors who have advocated the use of translation in FLT, it is argued that translation can effectively supplement the development of the four traditional language skills and, moreover, that some of the insights developed by TS can effectively be integrated into FLT as strategies aimed at enhancing leaners' cross-cultural communicative competences. To this purpose, selected insights from TS (e.g. the functional approach and the skopos theory, the cultureme model, the theory of memes) are discussed and their potential for creating synergies with FLT are explored. Finally, the paper discusses the omnipresence of different forms of translation and interpreting in contemporary societies and shows that this naturally and logically calls for a systematic inclusion of translation in FLT.
Keywords: didactique des langues; didaktika jezika; enseignement des langues; jezikovni pouk; kulturem; mem; prevajanje; skopos; traduction; translation; tuji jeziki